La metodologia medica in psicoterapia. L’interpretazione - Anzilotti, Carlo (Il sogno della farfalla, 2022)
The aim of this paper is to analyze the concept of interpretation, drawing from the concept of ‘intuition’ proposed by the psychiatrist Massimo Fagioli. Starting from the theoretical elaborations exposed in the volume Death instinct and knowledge until the subsequent writings published from 2006, the author of this paper traces the research carried out on the psychotherapist’s mental attitude which is required for the treatment to cure.